Meningkatkan Minat Serta Hasil Belajar PAI Dan BP Melalui Metode Diskusi Kelompok - Susi Mar’atun Salichah (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2021)
The purpose of this study was to increase the interest and learning outcomes of fifth grade students at SDN Sidamulya 01 in PAI and BP learning using the group discussion method. The type of research is Classroom Action Research (CAR). This study uses the Kemmis and Mc. Taggart. The research subjects were 14. Data collection techniques were test, observation and documentation techniques. Validation of data by triangulation technique Data analysis method using qualitative data analysis. The results of the study prove that the use of group discussion methods can increase student interest, showing the acquisition in the initial study of 6 students (42.86%) to 9 students or 64.29% and 13 students or 92.86% in the last cycle. Student learning outcomes from an average of 57.14 in the initial study, to 66.43, and in the second cycle to 76.43. The level of mastery learning just reached 4 students or 28.57% in the initial conditions, increased to 6 students or 42.86% and 13 students or 92.86% in the second cycle.